The relevance of resveratrol in ameliorating carotid atherosclerosis through glycolysis - Henan Pan; Zongkai Wu; Yaran Gao; Wentao Yao; Ge Feng; Hebo Wang (BMC Cardiovascular Disorders)
Abstract Background Atherosclerosis (AS) poses a pressing challenge in contemporary medicine. Glycolysis is a crucial bioenergetic metabolic pathway that provides the primary energy source for endothelial cells. Resveratrol (Res) is a natural compound that has been shown to possess AS. However, the underlying mechanisms of its anti-atherosclerotic effects are not yet fully understood. Methods We established a balloon injury model of the common carotid artery in Sprague-Dawley (SD) rats and an ox-LDL endothelial cell injury model for in vivo and in vitro experiments, respectively. Results Our study showed that 14 days after balloon-induced injury to the carotid intima of SD rats in vitro, the levels of glycolysis-related proteins fructose-2,6-bisphosphatase 3 (PFKFB3), glucose transporter 1 (GLUT1) and hexokinase 2 (HK2) were increased. Meanwhile, Res treatment improved intimal hyperplasia and reduced the levels of expression of these glycolysis-related proteins, and with higher concentrations of Res leading to more pronounced improvements. In vivo, in ox-LDL HUVECs, Res reduced glucose uptake and lactate production, inhibited apoptosis, and decreased the expression of PFKFB3, GLUT1, HK2, and p-AKT. After the addition of a phosphatidylinositol 3-kinase (PI3K) inhibitor, the we established a balloon injury model of the common carotid artery in SD rats and an ox-LDL endothelial cell injury model for in vivo and in vitro experiments, respectively, and expression levels of p-AKT were observed to increase. Conclusion According to these findings, Resveratrol can reduce AS by influencing glycolysis and inhibiting apoptosis through the PI3K-AKT signalling pathway.